Marketing Communication Implementation to Increase Visitors - Dewi Kamalia Wahyuni; Cecep Safa’atul Barkah (Universitas Ciputra Surabaya, 2024)
Kampus Merdeka provides students with opportunities to learn entrepreneurial skills. As part of its implementation, a bazaar is established as a platform for students to gain practical entrepreneurial experience. To optimize this practice, the committee must attract visitors to the bazaar through promotional activities. This research aims to analyze the implementation of promotional activities conducted by the committee using marketing communication strategies. The method employed is qualitative research with a descriptive approach, utilizing primary data sources. The findings reveal that marketing communication strategies executed through advertising, sales promotion, direct selling, and events have been carried out adequately but not optimally, and marketing through personal selling channels has not been utilized, resulting in the failure to reach the targeted number of visitors. It is recommended that promotional activities be intensified with a wider reach, and close collaboration between the committee and participants of the Wirausaha Merdeka program is essential for promoting the bazaar effectively.